Occupational risk perception of construction workers: a cross sectional study - Mastrantonio, Riccardo; Cofini, Vincenza; Mastrangeli, Giada; Pettinaro, Mauro; Mastrodomenico, Marianna; Fabiani, Leila (Frontiers in Public Health, 2024)
Introduction Construction workers are often exposed to significant injury risk. The aim of our study is to assess their occupational hazards and injury risk perception. Methods We administered 256 questionnaires to construction workers. The survey was aimed at collecting information regarding occupational risk and hazard exposure perception, risk control and behavioral self-assessment. We analyzed the data obtained in order to highlight any associations between injury risk perception and anamnestic, occupational, behavioral or perceptual factors. Results Participants were prevalently males (92.37%) aged 21–60 years (94%). They showed a job seniority level of 21.3 (11.51) on average and, ranging from a 1 to 10 score, a danger awareness of 6.8 (2.9), a lack of prevention measures 6.0 (3.3), an improper behavior of 7.3 (2.7), an unpredictable fate of 6.0 (2.9). These factors resulted significantly associated with the injury risk perception. Multivariable analysis highlighted that the injury risk perception was associated with the lack of prevention measure and unpredictable fate. On the other hand, we found a negative association with the workers’ improper behaviors. Conclusion Workers’ perception showed fairly uniform average values even when occupational risk was demonstrated. Our analysis suggests a positive correlation between injury risk perception and the idea that injuries are due both to fate and to chance; it also shows a negative correlation between injury risk perception and the idea that injuries are due to improper behavior. A lack of fully comparable studies confirms the need for further studies on the injury risk perception of construction workers.